1997
DOI: 10.1017/s1357729800008729
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extensive feeding on α-tocopherol concentration and oxidative stability of muscle microsomes from Iberian pigs

Abstract: The effect of extensive feeding, confinement and diet supplementation with a-tocopheryl acetate (100 mg/kg) on the fatty acid composition and tocopherol concentration of microsome extracts and their susceptibility to oxidation was studied in Iberian pigs. The diet of pigs raised extensively was mostly composed of acorn and grass. The a-tocopherol contents of acorn and grass were 20 and 171 mg/kg dry matter, respectively. Microsomal fatty acid composition showed no differences among groups. Pigs feeding extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
31
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 19 publications
15
31
0
1
Order By: Relevance
“…Acorns contain high level of C18:1 (higher than 60% of fatty acids, Rey et al, 1997). This would suggest that some dietary fatty acids could cross the porcine placenta, in agreement with Gerfault et al (1999) and Rooke et al (2001).…”
Section: Discussionsupporting
confidence: 84%
“…Acorns contain high level of C18:1 (higher than 60% of fatty acids, Rey et al, 1997). This would suggest that some dietary fatty acids could cross the porcine placenta, in agreement with Gerfault et al (1999) and Rooke et al (2001).…”
Section: Discussionsupporting
confidence: 84%
“…These results are in accordance with Rey et al (2006), but Cava et al (1997) and Daza et al (2005a) observed a higher C18 :1 n-9 proportion in longissimus dorsi intramuscular PL in Iberian pigs raised under free-range conditions than in those fed a formulated diet in confinement. However, Rey et al (1997) were unable to detect differences in C18:1 n-9, C18:2 n-6, n-6 and n-3 proportions in microsome extracts from longissimus dorsi muscle when free-range and mixed diet fed pigs were compared. 1,2,3,4,5,6 -explanation see Table 2 The liver fat (LF) percentages were 6.…”
Section: Resultsmentioning
confidence: 86%
“…Pentadecenoic acid (C15:1) (Sigma, Alcobendas, Madrid, Spain) was used as internal standard. Previously, methylated FA samples were identified according to Rey et al (1997) using a gas chromatograph (Model HP6890; Hewlett Packard Co., Avondale, PA, USA) and a 30 m × 0.32 mm × 0.25 μm cross-linked polyethylene glycol capillary column (Hewlett Packard Innowax, Avondale, PA, USA). A temperature programme of 170°C to 245°C was used.…”
Section: Methodsmentioning
confidence: 99%